Decolonizing Possibilities in Special Education Services - Yee, Nikki L.; Butler, Deborah L. (Canadian Journal of Education/Revue canadienne de l’éducation, 2020)
Colonial contexts continue to shape the experiences of Indigenous students, especially in special education, even as educators work to respond to Indigenous perspectives. In this article we first apply a decolonizing critique to consider how colonialism affects special education programming, then survey Indigenous and decolonizing scholarship to (re)imagine how educators may start to address these concerns. Our analysis suggests that educators (1) engage in critical self-examination, (2) adopt holistic assessment strategies, (3) explore teaching practices emerging from decolonizing perspectives, and (4) examine and (re)imagine service delivery models. Educators may use these ideas as a springboard for exploring more contextualized decolonizing possibilities. Keywords: inclusive education, special education, decolonization